2011
DOI: 10.1001/jama.2011.1590
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Alcohol Consumption During Adult Life, Drinking Patterns, and Breast Cancer Risk

Abstract: Context Multiple studies have linked alcohol consumption to breast cancer risk, but the risk of lower levels of consumption has not been well quantified. In addition, the role of drinking patterns (i.e. frequency of drinking and “binge” drinking) and consumption at different times of adult life are not well understood. Objective To evaluate the association of breast cancer with alcohol consumption during adult life, including quantity, frequency, and age at consumption. Design, Setting, and Participants Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
324
4
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 430 publications
(360 citation statements)
references
References 42 publications
17
324
4
15
Order By: Relevance
“…Our studies have demonstrated that alcohol increases Brf1 expression and Pol III gene transcription to facilitate cell transformation and tumor formation (Zhang et al ., 2013; Zhong et al ., 2011, 2016). BRCA1 is a tumor suppressor (Duncan et al ., 1998; Yoshida and Miki, 2004), which is responsible for repairing damaged DNA (Chen et al ., 2011). Women with an abnormal BRCA1 gene have up to an 80% higher risk of developing breast cancer (Friendenson, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have demonstrated that alcohol increases Brf1 expression and Pol III gene transcription to facilitate cell transformation and tumor formation (Zhang et al ., 2013; Zhong et al ., 2011, 2016). BRCA1 is a tumor suppressor (Duncan et al ., 1998; Yoshida and Miki, 2004), which is responsible for repairing damaged DNA (Chen et al ., 2011). Women with an abnormal BRCA1 gene have up to an 80% higher risk of developing breast cancer (Friendenson, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, the mechanism(s) underlying this association remains unclear. One potential mechanism relates to the impact of alcohol on folate metabolism; alcohol may hinder the bioavailability of dietary folate, 4 particularly in heavy drinkers.…”
mentioning
confidence: 99%
“…I know of only 3 bona fide environmental breast carcinogens: ionizing radiation 13 , hrt 10,11 , and alcohol 14 . Of those three, only radiation is clearly mutagenic, and the period of highest sensitivity is between menarche and age 18.…”
mentioning
confidence: 99%